Understanding the dynamics of household solar PV adoption in Uzbekistan - Abdikarimova, Dinara; Ibragimov, Abdulla; Sidique, Shaufique F.; Arifuzzaman, Md; Brindal, Mark (Elsevier B.V., 2026)
Uzbekistan is embarking on a transition in renewable energy to meet its 2030 goals of reducing greenhouse gas emissions by 35% and increasing the share of renewables in electricity generation to more than 50%. Although there is considerable potential for solar energy, the uptake of solar photovoltaic (PV) systems in residential settings is hindered by financial, regulatory, and behavioral challenges. This study employs a system dynamics approach to assess the impact of various policy interventions—specifically feed-in tariffs, tax exemptions, installation rebates, subsidized loans, and green certificates—on the adoption of residential photovoltaic systems in Uzbekistan. The analysis utilizes a causal loop diagram alongside a stock and flow model developed in Vensim to simulate different scenarios, assessing the effects of these interventions on the enhancement of photovoltaic capacity, revenue generation, and the reduction of carbon dioxide emissions. The results demonstrate that subsidized loans represent the most efficient policy tool, promoting sustainable growth in photovoltaic adoption and achieving significant emissions reduction outcomes. The findings provide crucial information for decision-makers in Uzbekistan and similar developing nations. They emphasize the importance of direct financial assistance strategies to overcome investment challenges and accelerate the shift towards renewable energy. This study highlights the importance of system dynamics modeling as a key tool for developing effective and sustainable energy strategies.